Harnessing opportunities to enhance the distance learning experience of MSW students: an appreciative inquiry process. Issue 6 (18th August 2018) - Miles, Debra; Mensinga, Jo; Zuchowski, Ines
Abstract: Despite a long history of engagement with distance education models in Australia, the adoption of distance learning in social work education has been cautious and social work educators' ability to teach and develop relationship-based skills in distance and online environments, is consistently questioned. This paper reports on a research project conducted with staff and students of a regional Australian university offering a qualifying Master of Social Work program through blended learning models. Underpinned by a framework of Appreciative Inquiry, the project employed focus groups and semi-structured interviews with staff and an online survey with students to identify issues of concern and to inform the redesign of course delivery. Pivotal to students' experience was the need to create a sense of cohort to overcome perceptions of isolation and abandonment when subjects are delivered in distance modes rather than face to face. Moreover, inaccurate assumptions about postgraduate students' familiarity with basic academic conventions and online teaching strategies were seen to contribute to a sense of personal failure and incompetence that could lead to withdrawal from the course. Strategies and processes introduced to address these matters are discussed and preliminary evaluations of their impact shared.